DAMPAK GAME ONLINE TERHADAP KONSENTRASI DAN HASIL BELAJAR SISWA DI KELAS - Samsudin; Babang Robandi; Siti Halimah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The rapid advancement of digital technology has led to the rise of online gaming, which has significantly affected various aspects of daily life, including education. This study aims to analyze the impact of online games on students' concentration and academic performance in the classroom. Online games can have both positive and negative effects on students. On the positive side, certain games are designed to enhance cognitive skills, such as critical thinking, strategy, and teamwork. However, the negative effects are more pronounced in students who become addicted to online gaming. Excessive time spent playing games can interfere with study time, reduce concentration in class, and hinder academic achievement. Students who frequently play online games tend to be more easily distracted, struggle to maintain focus, and become disengaged during lessons. Research findings indicate a significant negative correlation between the amount of time spent playing online games and academic performance. Students who spend longer hours gaming tend to have lower academic scores compared to those who game less. Therefore, it is crucial for schools and parents to monitor online game usage and set appropriate time limits to prevent it from disrupting effective learning.